Постать Юрія Косача на шпальтах часопису “Неділя” (Ашаффенбург) - Дмитрук, О. (Слово і Час, 2009)
У статті подано огляд публікацій газети “Неділя” (“The Sunday” – Ukrainian Weekly, Український
незалежний часопис, Ашаффенбург, друга половина 40-х – перша половина 50-х років ХХ століття),
темою яких був МУР, життєва і творча доля його діячів, особливо Юрія Косача. In the article, the author reviews the publications of Ukrainian independent periodical “Nedilia” (“The Sunday”
– Ukrainian Weekly; was published in Aschaffenburg in the second half of the 1940’s – the first half of the
1950’s) thematising the so-called “Mystetzky Ukrainsky Rukh” (Ukrainian Art Movement) as well as the life and
works of its members, especially those of Yuriy Kosach. В статье предлагается обзор публикаций
газеты “Нэдиля” (“Воскресенье”, “The Sunday” –
Ukrainian Weekly, Украинский независимый журнал,
Ашаффенбург, вторая половина 40-х – первая
половина 50-х годов ХХ ст.), темой которых был
“МУР” (“Украинское Движение Искусства”), жизненный
и творческий путь его участников, особенно Юрия
Косача.